TRANSFORMASI KOMPETENSI GURU MELALUI PENGENALAN KONSEP KODING DAN KECERDASAN ARTIFISIAL PADA PEMBELAJARAN LINTAS DISIPLIN - Ida Ayu Putu Febri Imawati; Ni Ketut Erawati; Luh Putu Risma Noviana; Ni Kadek Rini Purwati; I Wayan Dika (Sewagati, 2025)
A workshop was conducted to enhance digital literacy and foundational knowledge of coding and artificial intelligence (AI) among subject teachers at Denpasar 4 Public High School. The initiative addressed the need to strengthen educators' competence in integrating digital technology and AI into interdisciplinary instruction. The workshop featured interactive, hands-on sessions. Training materials included introductions to plugged-in, unplugged, and internet-based coding, fundamental AI concepts, prompt engineering for content creation, and the use of Teachable Machine for simple AI exploration. Teachers engaged in discussions and applied these concepts within their respective disciplines, including mathematics, language, and social studies. The outcomes indicated a substantial improvement in teachers' understanding of basic coding principles and the potential of AI as a creative instructional tool. The workshop also enhanced teachers' capacity to address educational challenges and advance digital transformation.